ANALISIS KIMIA 18 JENIS KAYU KURANG DIKENAL DARI JAWA BARAT - Gustan Pari Pari (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
This paper deals with chemieal analyses of eighteen lesser known wood species from West Java. The analyses comprise of the determination of holocellulose, cellulose, lignin, pentosan, moisture content, ash. content, silica content and the solubility in cold water, hot water, one percent of sodium hydroxide and alcohol benzerui extractiue. These analyses were conducted to determine their basic characteristics and ultimate uses of the wood. The result shows that holocellulose content ranges from 52,45 - 73,69 percent, cellulose from 42,87-58,54 percent, lignin from 20,0 - 31,42 percent, pentosan from 12,09 - 18,46 percent, moisture content from 6,84 - 18,62 percent, ash content from 0,23 - 1,92 persent, silica content from 0,11 - 0,74 percent. The solubility in cold water ranges from 0,80 - 8,57 percent, hot water from 0,84 - 9,64 percent, in one percent sodium hydroxide solution from 9,07 - 30,34 percent and in alcohol benzena (1:2) from 0,99 - 11,49 percent. Based on chemical analyses, especially the cellulose content, the 18 lesserknown wood species from West Java are suitable as raw material for pulp and paper industry.